Supply Chain Management Practices in Response to Ecosystem Challenges – Literature Review - Ihssane El Hajjaji; Hasnae Rahmani (European Scientific Journal, ESJ, 2025)
In recent years, there has been a widespread awareness of issues affecting the ecosystem, such as climate change. It is in fact a universal reality that affects human life, business activities, and the environment. In this context, companies are required to master operations in a dynamic and risky ecosystem where logistics play a very important role in meeting sustainable development objectives. More specifically, optimizing supply chain performance requires the implementation of various green practices, which leads managers to rethink their decision-making processes related to supply chain management in order to reduce carbon emissions and improve their overall performance (Wang and Sarkis, 2013). This study is therefore a direct continuation of work focusing on sustainable supply chain management. This type of management is now an obligation rather than a choice in the era of climate change, which has major implications in terms of strategic and operational planning. It therefore seems relevant to address the following question: “What supply chain management practices can be adopted to address the challenges of climate change?” The objective of this article is to identify best practices in supply chain management and their impact on the environment and overall performance. Our research methodology consists of a theoretical study based on an analysis of work carried out in this field, the identification of green SCM practices that should be adopted by companies, and an analysis of their impact on overall performance.